PECULIARITIES OF ECONOMIC RESILIENCE AS AN IMPORTANT SCIENTIFIC CATEGORY FOR ENSURING NATIONAL SECURITY - ІВАНОВ, Сергій (Київський національний університет імені Тараса Шевченка, 2024)
Background . Economic resilience has become an objective necessity that directly determines the states' prospects. The country's national security in economic terms involves the support of the national economy at the level of development that would provide opportunities for further economic growth and the ability to counteract the influence of external and internal threats. Intending to analyze economic resilience as a scientific category for ensuring national security and identifying its features, the author characterized economic resilience as a key component of national security and identified patterns and trends of modern economic development and destructive factors and threats to national security from an economic point of view and identified features of economic resilience. The object of the study was economic resilience as a category of ensuring national security. Methods . This publication is based on the use of various methods. Analysis and synthesis were used to characterize economic sustainability as a key component of national security. Deduction and induction helped to investigate patterns and trends of modern economic development and identify destructive factors and threats to national security. The systematic approach made it possible to understand the importance of economic stability in today's realities as an element of the country's national security. Results . Having analyzed economic resilience as a key category of national security, it was determined that economic resilience combines the ability to resist external factors, reduce vulnerability, and the ability of the economy to recover. Also, economic resilience implies a quick return to equilibrium and the ability of the economy to absorb shocks before changing its structure and to adapt to or react to shocks. The classification of destructive factors and threats to national security from an economic point of view into external and internal makes it possible to understand the reasons for the imbalance of the economy and to assess the ways of increasing economic resilience. Features of economic resilience include its complexity, but the possibility of measuring it based on different indicators and depending on the calculation method or model, the focus on balance and adaptation, and the usefulness of the economic resilience approach for understanding the costs and benefits of political intervention. Conclusions . Thus, economic resilience is a category that is necessary not only to define national security but also to measure and control it

Вступ . Наголошено, що економічна стійкість стала об'єктивною необхідністю, що безпосередньо визначає майбутні перспективи держав. Національна безпека країни в економічному плані передбачає підтримку національної економіки на тому щаблі розвитку, яка забезпечувала би можливості подальшого економічного зростання, здатність протидіяти впливу зовнішніх і внутрішніх загроз. З метою аналізу економічної стійкості як умови забезпечення національної безпеки і виявлення її особливостей, надано характеристику економічної стійкості як ключового складника національної безпеки, виявлено закономірності та тенденції сучасного розвитку економіки, а також деструктивні фактори та загрози національній безпеці з боку економіки, визначено особливості економічної стійкості. Об'єктом дослідження виступила економічна стійкість як складова забезпечення національної безпеки. Методи . Для характеристики економічної стійкості як ключового складника національної безпеки було використано методи аналізу та синтезу. Дедукція та індукція допомогли дослідити особливості та тенденції розвитку економіки на сучасному етапі та виявити деструктивні чинники та загрози національній безпеці. Системний підхід дозволив зрозуміти важливість економічної стійкості в реаліях сьогодення як елементу національної безпеки країни. Результати . Проаналізувавши економічну стійкість як складник національної безпеки, було визначено, що економічна стійкість поєднує здатність протистояти зовнішнім чинникам, знижувати вразливість та можливість економіки відновлюватись. Також доведено, що економічна стійкість передбачає швидке повернення до рівноваги та здатність економіки поглинати потрясіння до зміни своєї структури та адаптуватися до потрясінь чи реакції на них. Виявлено, що класифікація деструктивних чинників та загроз національній безпеці в економічному прояві на зовнішні та внутрішні дає можливість зрозуміти причини порушення рівноваги економіки, оцінити шляхи підвищення економічної стійкості. Розкрито, що до особливостей економічної стійкості слід зарахувати складність, але залежно від показників виміру, методу або моделі розрахунку фокус може бути на рівновазі та адаптації, що показує важливість економічної стійкості для розуміння витрат і переваг політичного втручання. Висновки . Визначено, що економічна стійкість є важливим складником, який потрібен не лише для визначення національної безпеки, а й її вимірювання та контролю.
ОСОБЛИВОСТІ ЕКОНОМІЧНОЇ СТІЙКОСТІ ЯК ВАЖЛИВОГО СКЛАДНИКА ЗАБЕЗПЕЧЕННЯ НАЦІОНАЛЬНОЇ БЕЗПЕКИ
Keywords: economic sustainability; national security; full-scale war; equilibrium; Total Economic Resilience Index.; економічна стійкість; національна безпека; повномасштабна війна; рівновага; індекс загальної економічної стійкості.